Croatian geomagnetic field maps for 2008.5 epoch - Mario Brkić (Annals of Geophysics, 2013)
The status of the Croatian Geomagnetic Repeat Stations Network (CGRSN) and Croatian Geomagnetic Network for Field Mapping (CGNFM), completed in 2010, was described. Standard and new survey practices as well as reduction techniques were presented. The CGRSN data reduced in reference to the L'Aquila (AQU), Grocka (GCK) and Tihany (THY) observatories using weighted averages were given for the epoch 2008.5. Detailed pictures of Dalmatia's geomagnetic field of 2008.5 and the corresponding anomaly, obtained from the CGNFM data were shown.